AI and Knowledge Management: Leveraging Machine Learning for Organizational Learning (International Journal of Food and Nutritional Sciences, 2021)
With the developments in the recent years where the awakening of Information communication technologies, the application of Artificial intelligence (AI) and knowledge management (KM) is becoming a success fundamental factor or organizational learning and performance. This research paper focuses on the topic, the application of a subcategory of Artificial intelligence known as machine learning for enhancing knowledge management in organizations. Based on the review of prior research and case studies, this paper defines the opportunities for using ML algorithms to support knowledge generation, dissemination, and utilization.